Collagen structural alterations contribute to stiffening of tissue after split-thickness skin grafting. - Rosin, Nicole L.; Agabalyan, Natacha; Olsen, Katherine; Martufi, Giampaol; Gabriel, Vincent; Biernaskie, Jeff; Di Martino, Elena S. (Wound Repair & Regeneration)
The gold standard treatment for full thickness injuries of the skin is autologous split-thickness skin grafting. This involves harvesting the epidermis and superficial dermis from healthy skin and transplanting it onto the prepared wound bed. The donor site regenerates spontaneously, but the appendages and cellular components from the dermal layer are excluded from the graft. As a result, the new tissue is inferior; the healed graft site is dry/itchy, has decreased elasticity, increased fragility, and altered sensory function. Because this dermal layer is composed of collagen and other extracellular matrix proteins, the aim was to characterize the changes in the dermal collagen after split thickness grafting that could contribute to a deficit in functionality. This will serve as a baseline for future studies designed to improve skin function using pharmacological or cell-based therapies for skin repair. A xenograft model whereby human split-thickness grafts were implanted into full-thickness defects on immunocompromised (athymic Nu/Nu) mice was used. The grafts were harvested 4 and 8 weeks later. The collagen microstructure was assessed with second harmonic generation with dual-photon microscopy and light polarization analysis. Collagen fiber stiffness and engagement stretch were estimated by fitting the results of biaxial mechanical tensile tests to a histo-mechanical constitutive model. The stiffness of the collagen fibril-proteoglycan complex increased from 682 ± 226 kPa/sr to 1016 ± 324 kPa/sr between 4 and 8 weeks postgrafting. At the microstructural level there were significant decreases in both thickness of collagen fibers (3.60 ± 0.34 μm vs. 2.10 ± 0.27 μm) and waviness ratio (2.04 ± 0.17 vs. 1.43 ± 0.08) of the collagen fibers postgrafting. The decrease of the macroscopic engagement stretch from 1.19 ± 0.11 to 1.09 ± 0.08 over time postgrafting mirrored the decrease in waviness measured at the microscopic level. This suggested that the integrity of the collagen fibers was compromised and contributed to the functional deficit of the skin postgrafting.